2023
DOI: 10.1177/18632521221149056
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric meniscal injuries: Current concepts

Abstract: Meniscal pathology is widely prevalent in the adult population, secondary to acute trauma and chronic degeneration. It is less commonly seen in children, although its incidence is rising. The true prevalence in children remains unknown, as pathologies such as discoid menisci often go undiagnosed, or are found only incidentally. The rising incidence can be attributed to increased participation in sports at younger ages, both in intensity and frequency, with potentially year-round competition. Meniscal tears lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…For patients who are experiencing symptoms such as blockages, pain, decreased quality of life and limitation to participate in sports, surgical treatment is recommended for their specific knee problem [29]. The surgical plan for a symptomatic DM should take into account the menisco-capsular peripheral stability, as classified by Ahn et al [30], as well as any other potential meniscal tears and concurrent injuries.…”
Section: Discussionmentioning
confidence: 99%
“…For patients who are experiencing symptoms such as blockages, pain, decreased quality of life and limitation to participate in sports, surgical treatment is recommended for their specific knee problem [29]. The surgical plan for a symptomatic DM should take into account the menisco-capsular peripheral stability, as classified by Ahn et al [30], as well as any other potential meniscal tears and concurrent injuries.…”
Section: Discussionmentioning
confidence: 99%
“…It is less common in pediatric patients, although studies have shown that meniscal injuries are on the rise even in children population [2][3][4]. This might be attributed to improved diagnostic availability and increased engagement in high-demand sports activities, which is known as the most common cause of meniscus tear situations in skeletally immature patients [2,5]. Previously, the most prevalent method of treating this pathology was arthroscopic partial meniscectomy [1].…”
Section: Introductionmentioning
confidence: 99%
“…To preserve as much meniscus tissue as possible, numerous repair methods were developed. Furthermore, it is crucial to provide appropriate treatment for meniscus tears in young individuals in order to prevent the eventual development of knee osteoarthritis following a meniscus injury [2]. Particularly in pediatric patients, meniscus repair procedures have been promising good and excellent outcomes due to better tissue healing potency [2,3].…”
Section: Introductionmentioning
confidence: 99%